Neurofeedback to enhance sleep quality and insomnia: a systematic review and meta-analysis of randomized clinical trials - Recio-Rodriguez, Jose I.; Fernandez-Crespo, Mei; Sanchez-Aguadero, Natalia; Gonzalez-Sanchez, Jesús; Garcia-Yu, Irene A.; Alonso-Dominguez, Rosario; Chiu, Hsiao-Yean; Tsai, Pei-Shan; Lee, Hsin-Chien; Rihuete-Galve, Maria I. (Frontiers in Neuroscience, 2024)
ObjectiveThis systematic review and meta-analysis of randomized-clinical trials aims to analyze the effect of interventions incorporating surface neurofeedback techniques on self-perceived sleep quality and insomnia in patients with or without sleep disturbances.MethodsThe review was completed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement and was deposited in the Prospero international prospective registry of systematic reviews (CRD42024528401). Seven clinical trials with different main outcomes but with pre-post intervention records of self-perceived sleep quality or insomnia symptoms assessed by questionnaires met our inclusion criteria, including a publication date within the last 10 years. Five trials investigated sleep quality through scores on the Pittsburgh sleep quality Index (PSQI) and three trials signs of insomnia severity assessed with validated scales. The methodological quality of the included studies was assessed using the Cochrane Collaboration’s tool for assessing the risk of bias and showed a high quality of them.ResultsA total of 5 studies that evaluated sleep quality with the PSQI total score were included in the meta-analysis. The results revealed that control conditions succeeded in improving PSQI-assessed sleep quality more than the analyzed Neurofeedback interventions (PSQI total score 0.57; 95% CI 0.13 to 1.01; p = 0.01). On the other hand, a total of 3 studies that evaluated insomnia severity with various insomnia scales were included in the meta-analysis The results revealed that neither the NF interventions nor the control conditions show a favorable outcome relative to each other (−0.13; 95% CI −0.44 to 0.18; p = 0.41).ConclusionThe interventions studied mostly apply a neurofeedback training protocol based on maintaining alpha waves in a range between 8 and 12 Hz, with electrode positioning in the frontal area or in the sensorimotor cortex and with a number of neurofeedback sessions ranging from 8 to 20 sessions. The meta-analysis showed that interventions incorporating surface neurofeedback do not produce additional benefits in self-perception of sleep quality or insomnia compared to a wide variety of control conditions including cognitive behavioral treatment or other biofeedback modalities.Systematic review registrationPROSPERO – International prospective register of systematic reviews – CRD42024528401 https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=528401.